EFFECT OF STARVATION AND INFESTATION BEHAVIOR OF LARVAE KHAPRA BEETLE, Trogoderma granarium Everts (COLEOPTERA : DERMESTIDAE) - Haris Setyaningrum (Gontor AGROTECH Science Journal, 2015)
The Khapra beetle Trogoderma granarium Everts is very destructive pest in various stored product and nominated as one of the hundred worst invasive species in the world. The study of starvation and infestation behaviors are important for improvement of insect control method. This study represent the number of molting as fact of regressive molting in starved condition, the larva of T. granarium within 68 days periods can be molted 1-3 times. The infestation behavior on three diets treatment presented. In grain wheat their larva are laid off the casting skin over the surface of product and distributed randomly in whole part of stored product. Respectively in flour casting skin are laid down in bottom of the container as effect of feeding. In flour the casting skin are laid on mostly over surface of the flour mixed with frass. In toilet tissue the infestation is present in hole over the surface and randomly position of casting skin.